UPAYA MENINGKATKAN HASIL BELAJAR DAN KREATIVITAS SISWA DALAM PEMBELAJARAN IPS MELALUI MODEL TREFFINGER PADA KELAS V SD MUHAMMADIYAH AMBARKETAWANG 2 TAHUN PELAJARAN 2016/2017 - Fiyanto, Arif; Ulfah, Amaliyah (universitas Ahmad Dahlan, 2018)
Background research low learning outcomes and creativity of students on subjects IPS class VSD Muhammadiyah Ambarketawang 2. Caused lessons dominated by teachers and less variation oflearning models. The purpose of research: 1) to know the improvement of student learningoutcomes in learning social studies using the model of learning Treffinger on students of class V 2)to know the improvement of student's creativity in learning IPS by using the model of learningTreffinger on students of class V.The type of research is Classroom Action Research (PTK). Implemented in 2 cycles, eachcycle consists of two meetings. Each cycle through 4 stages of planning, implementation,observation and reflection. The subjects of the study were students of class V of 25 students.Techniques of collecting observation, test, and documentation data. Data analysis usingquantitative and descriptive qualitative analysis. The success criteria of action is marked by theincrease of learning result that is 75% of students reach KKM score established by the school thatis 70. The success criteria of action is also seen from the creativity percentage of students that is75% of students included in good criterion (score ≥ 26).The results showed the results of learning and creativity of students in IPS learning using theTreffinger learning model has increased. Completeness of learning outcomes in the pre cycle of 8students (32%), completeness in the cycle 1 to 14 students (56%), and completeness in cycle 2 of 21students (84%). The result of students' creativity in the pre cycle there are 4 students (16%) gotscore ≥ 26, in cycle I there are 12 students (48%), in cycle II there are 20 students (80%). Theresults can be concluded that the Treffinger model can improve student learning outcomes andcreativity in learning IPS class V SD Muhammadiyah Ambarketawang 2.